Analysis of the Implementation of the Smoking Prevention Program for Middle School Students in the Maliku Health Center Work Area Year 2024 - Septiana Dewi; Nur Rizky Ramadani (Jurnal EduHealth, 2025)
Smoking behavior among adolescents is a significant public health issue worldwide. Maliku Health Center, as one of the health service centers in Maliku District, Pulang Pisau Regency, has implemented a smoking prevention program at the school level to reduce the prevalence of smoking behavior among students. However, the effectiveness of this program needs to be evaluated to ensure the impact and sustainability of the program in overcoming smoking behavior in students. This study aims to analyze the implementation of a smoking prevention program for middle school students in the Maliku Health Center working area in 2024. Methods: This research is a qualitative research with a case study type. Data collection through in-depth interviews, observations and documentation. Data analysis includes the process of organizing, analyzing, and interpreting non-numerical data into a conclusion information. Results: The smoking prevention program in secondary schools in the Maliku Health Center area has succeeded in increasing students' understanding of the dangers of smoking. Through counseling, training, and regular campaigns, many students have begun to understand the health risks posed by smoking. Student participation in educational activities is also quite high, with more than 500 students actively involved and more than 100 educational materials distributed. However, long-term behavioral change still requires ongoing support from schools, parents, and health workers. Strengthening educational methods and intensifying activities need to be done so that program results can be more optimal. Conclusion : The program increases student awareness, but sustainable behavioral changes require intensive mentoring and ongoing support from various parties.